Learning Media Based on Development of ICT (Information Communication Technology) in Increasing Student Motivation and Learning Outcomes in Indonesian Language Subject - Rohana Hariana Intiana, Siti; Amalia Prihartini, Arina; Handayani, Fitriana; Faridi, Kharul (BULLET : Jurnal Multidisiplin Ilmu, 2024)
The objective of this study is to demonstrate the advantages of utilizing ICT (Information and Communication Technology) learning tools in the context of studying Indonesian Language Subject and to examine its impact on student motivation and academic performance. With the advent of the Fourth Industrial Revolution, traditional ways of learning are no longer necessary, particularly when it comes to selecting educational resources. Due to technological advancements, learning media has evolved into digital formats that cater to many elements of education. This educational approach is commonly referred to as ICT-based learning, which stands for information and communication technology-based learning. It enables students to study from any location, unrestricted by the confines of traditional classroom settings, in order to access the most up-to-date material. The use of educational media significantly impacts the student learning process by facilitating learning activities, enhancing motivation, and improving student learning outcomes. The research methodology employed in this study is a comprehensive literature review. The data gathering process involved using Google Scholars to select publications that focused on ICT (Information and Communication Technology) learning media in Indonesian language learning and its impact on student motivation and learning results. The outcome of this study is an Indonesian language acquisition model that may be implemented by incorporating the Indonesian language learning model (listening, speaking, reading, and writing) with ICT media (computers, internet, multimedia). Research has demonstrated that the implementation of ICT-based learning has a positive impact on student motivation and learning outcomes, as seen by improvements in average student grades and increased passion for learning. In order to achieve success and overcome barriers, the use of ICT in learning must undergo a process that includes planning, development, evaluation, and revision stages. This process involves the participation of numerous educational actors.